ОБРЯДЫ ЛЕНКОРАНСКОЙ ЗОНЫ АЗЕРБАЙДЖАНА (Journal of Oriental Studies, 2016)
Әзірбайжандағы дәстүрлі некелесу этнографиялықәдебиеттерде және халық арасында «той салтанаты»(«той-дюйун») деп аталады. Нақтылы кезеңдерден тұра-тын үйлену тойы түрлі салт-дәстүрді, әдеп-ғұрыптардыбіріктіреді.The article has been written on the base of outerethnographic and literary materials. Past traditional weddingcustoms of the Lankaran region of Azerbaijan areinvestigated here. All the stages of wedding are described inthe article and compared with the wedding traditions ofsome neighbouring peoples.